Caffeic Acid Inhibits Tumour Mass Formation in MG-63 Cells-induced Nude Mice - Ferry Sandra; Dewi Ranggaini; Nurrani Mustika Dewi; Melanie Sadono Djamil; Laifa Annisa Hendarmin (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Formation of tumour mass is one symptom of osteosarcoma development. Caffeic acid has been known to provide effective treatment but has less side effect for some cancer therapy. Studies reported that caffeic acid might promote apoptosis in MG-63 osteosarcoma cells, however, the effect of caffeic acid treatment in preventing tumour mass formation has not been well elucidated, especially in MG-63 cells-induced nude mice in vivo.METHODS: MG-63 cells were pre-treated with 0, 1, or 10 µg/mL caffeic acid, and 6 hours after pre-treatment, MG-63 cells were injected into subcutaneous space of mice to induce osteosarcoma. Another model was also created by subcutaneously injecting MG-63 cells to the back of mice, and after 48 days, the visible tumour mass was injected intra-tumour with 0 or 10 µg/mL caffeic acid every 7 days for 6 times. After 90 days, mice were anaesthetised, and the nodule pictures were taken for observation and measurement. RESULTS: In pre-treated MG-63 cells-induced mice, volumes of the mass decreased in reverse with the dose of caffeic acid given. Ten µg/mL caffeic acid pre-treatment was able to significantly lower the mass volume compared to the untreated (p<0.05). Meanwhile, the intra-tumour treatment of 10 µg/mL caffeic acid, even though not significant, was able to inhibit tumour mass formation.CONCLUSION: Results of caffeic acid pre-treatment and caffeic acid treatment in tumour mass of mice show that caffeic acid is able to inhibit the MG-63 cells formation. This suggests that caffeic acid can be a potential anti-cancer agent.KEYWORDS: caffeic acid, osteosarcoma, MG-63 cells, tumour mass